Diagnosis and Management of Lumbar Spinal Stenosis: A Review - Katz, Jeffrey N; Zimmerman, Zoe E; Mass, Hanna; Makhni, Melvin C (JAMA : the journal of the American Medical Association, 2022)
Lumbar spinal stenosis is a prevalent and disabling cause of low back and leg pain in older persons, affecting an estimated 103 million persons worldwide. Most are treated nonoperatively. Approximately 600 000 surgical procedures are performed in the US each year for lumbar spinal stenosis. The prevalence of the clinical syndrome of lumbar spinal stenosis in US adults is approximately 11% and increases with age. The diagnosis can generally be made based on a clinical history of back and lower extremity pain that is provoked by lumbar extension, relieved by lumbar flexion, and confirmed with cross-sectional imaging, such as computed tomography or magnetic resonance imaging (MRI). Nonoperative treatment includes activity modification such as reducing periods of standing or walking, oral medications to diminish pain such as nonsteroidal anti-inflammatory drugs (NSAIDs), and physical therapy. In a series of patients with lumbar spinal stenosis followed up for up to 3 years without operative intervention, approximately one-third of patients reported improvement, approximately 50% reported no change in symptoms, and approximately 10% to 20% of patients reported that their back pain, leg pain, and walking were worse. Long-term benefits of epidural steroid injections for lumbar spinal stenosis have not been demonstrated. Surgery appears effective in carefully selected patients with back, buttock, and lower extremity pain who do not improve with conservative management. For example, in a randomized trial of 94 participants with symptomatic and radiographic degenerative lumbar spinal stenosis, decompressive laminectomy improved symptoms more than nonoperative therapy (difference, 7.8 points; 95% CI, 0.8-14.9; minimum clinically important difference, 10-12.8) on the Oswestry Disability Index (score range, 0-100). Among persons with lumbar spinal stenosis and concomitant spondylolisthesis, lumbar fusion increased symptom resolution in 1 trial (difference, 5.7 points; 95% CI, 0.1 to 11.3) on the 36-Item Short Form Health Survey physical dimension score (range, 0-100), but 2 other trials showed either no important differences between the 2 therapies or noninferiority of lumbar decompression alone compared with lumbar decompression plus spinal fusion (MCID, 2-4.9 points). In a noninferiority trial, 71.4% treated with lumbar decompression alone vs 72.9% of those receiving decompression plus fusion achieved a 30% or more reduction in Oswestry Disability Index score, consistent with the prespecified noninferiority hypothesis. Fusion is associated with greater risk of complications such as blood loss, infection, longer hospital stays, and higher costs. Thus, the precise indications for concomitant lumbar fusion in persons with lumbar spinal stenosis and spondylolisthesis remain unclear. Lumbar spinal stenosis affects approximately 103 million people worldwide and 11% of older adults in the US. First-line therapy is activity modification, analgesia, and physical therapy. Long-term benefits from epidural steroid injections have not been established. Selected patients with continued pain and activity limitation may be candidates for decompressive surgery.